"Bali-Kang": A Minimalist Music with Western, Balinese, and Chinese Elements - Ni Putu Verenita Sintya Devi; Ni Wayan Ardini; Wahyu Sri Wiyati; Ricky Irawan (Journal of Music Science, Technology, and Industry, 2021)
Purpose: This paper is to remind the Balinese folklore of the legendary love story of King Jaya Pangus Harkajalancana and Paduka Sri Cacangkaja Cihna (Kang Cing Wie) in Dalem Balingkang by composing a minimalist music with Western, Balinese, and Chinese elements. Research methods: The musical work is done by referring to the exploration stage, the experimental (improvisation) stage, and the forming stage. The three stages are applied as a reference in the process of cultivating the â€œBali-Kangâ€. Results and discussion: The â€œBali-Kangâ€ composition consists of three parts with a different interpretation but is still in one unity. This work uses minimalist music techniques and kotekan techniques, which last for about 14 minutes. Implication: Such a music must always be made update according to newest and actual situation so that the legendary love story can be remembered by all generations, at least in Bali.